MODIFIKASI SISTEM KENDALI SEPEDA LISTRIK LISTRIK HYBRID - Nurul Huda; Fahrul Khamami (Cahaya Bagaskara : Jurnal Ilmiah Teknik Elektronika, 2017)
Energy can not be created and destroyed, but the energy can be converted from one form to another form. The application of the law of conservation of energy can be seen in everyday life. On a power generator that is often used in part of the community in the supply of electricity from the PLN has stopped, when the generator is turned on then it will transform kinetic energy into electrical energy.The workings of electric machine principle regenerative (refill/recharging while the vehicle is in operation) on a hybrid engine, in contrast to the full power of the bike. The bike can not recharge electricity. When electricity runs out, the Battery/batteries should be incharge specifically with a time of 8 to 12 hours (for the technology onboard charger). Special electric machine hybrid, the engine could recharge to aki by using kinetic energy with the help of a generator mounted on the electric bicycle. With an operating system like this so added a power supply will occur.On the genset hybrid that functions as the power plant to supply batteries or battery which is then transmitted to the DC motor bikes. the generator never directly into propulsion vehicles. System working on hybrid begins from the generator, and the resulting power generators are distributed to the battery and the DC motor is transmitted to the bike. then moving the wheel.